Investment policy review : Dominican Republic (UN New YorkUS, 2009)
Provides an overview of foreign direct investment trends and impact and examines the investment framework. Proposes a new investment promotion framework in order to attract the foreign investment necessary to move up the value chain.
Keywords: INVESTMENT POLICY